Student lodges report against UPM guards - The Sun, Kong See Hoh (2007)
A student of Universiti Putra Malaysia (UPM) who twice aborted attempts to make police reports on Saturday for the return of his laptop, hand phone and other belongings seized bu the universiti's security personnel, lodged a report yesterday.